Attenuation and reinforcement mechanisms over the life course - Matteo Richiardi; Patryk Bronka; Justin van de Ven (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2024)
We analyse the complex dynamic feedback effects between different life domains over the life course, providing a quantification of the direct (not mediated) and indirect (mediated) effects. To extend the analysis in scope and time beyond limitation of existing data, we use a rich dynamic microsimulation model of individual life course trajectories parameterised and validated to the UK context. We interpret findings in terms of the implied attenuation or reinforcement mechanisms at play, and discuss implications for health and economic inequalities.
Keywords: C15; C63; C99; D30; R20; 330; Dynamic microsimulation; feedback mechanisms; life course analysis; life events; mediation analysis